Mechanism of Apoptosis Induction by Mycoplasmal Nuclease MGA_0676 in Chicken Embryo Fibroblasts - Li, Peng; Xu, Jian; Rao, Hong-mei; Li, Xia; Zhang, Yun-ke; Jiang, Fei; Wu, Wen-xue (Frontiers in Cellular and Infection Microbiology, 2018)
MGA_0676 has been characterized as a Mycoplasma gallisepticum nuclease that can induce apoptosis of chicken cells. However, the mechanism by which MGA_0676 induces apoptosis has remained unclear. In this study, we evaluated MGA_0676-induced apoptosis and internalization in immortalized chicken embryo fibroblasts (DF-1) and cancer cell lines. The internalization of MGA_0676 was proven through caveolin-mediated endocytosis by blocking the endocytosis with specific inhibitors or with siRNA. We identified the Thif domain of NEDD8-activating enzyme E1 regulatory subunit (NAE) in DF-1 as the target region interacting with the SNC domain of MGA_0676. The interaction between the Thif and SNC domains was observed co-located in the perinuclear and nuclear of DF-1. We found that the interaction between NAE and MGA_0676 increased the ability of apoptosis and accelerated the process of cullin neddylation in DF-1 cells, in turn activating NF-κB. This resulted in the observed aggregation of NF-κB in the nuclei of DF-1 cells. Moreover, the apoptosis induced by MGA_0676 decreased significantly when NF-κB was inhibited by siRNA or BAY 11-7082 or when NAE was silenced by siRNA. Overall, our results demonstrate that MGA_0676 is internalized through caveolin-mediated endocytosis, interacts with SNC-dependent Thif to accelerate the process of cullin neddylation and activates NF-κB in DF-1 cells, ultimately playing a key role in apoptosis in chicken cells. Our results indicate MGA_0676 constitutes a critical etiological virulence factor of the respiratory disease caused by M. gallisepticum. This study also opens a venue to investigate MGA_0676 as a potential candidate as pro-apoptotic drug in cancer studies.